Effects of the soil microbiome on the demography of two annual prairie plants. Issue 13 (14th June 2020) - Reynolds, Hannah S.; Wagner, Rebekah; Wang, Guangzhou; Burrill, Haley M.; Bever, James D.; Alexander, Helen M.
Abstract: Both mutualistic and pathogenic soil microbes are known to play important roles in shaping the fitness of plants, likely affecting plants at different life cycle stages. In order to investigate the differential effects of native soil mutualists and pathogens on plant fitness, we compared survival and reproduction of two annual tallgrass prairie plant species ( Chamaecrista fasciculata and Coreopsis tinctoria ) in a field study using 3 soil inocula treatments containing different compositions of microbes. The soil inocula types included fresh native whole soil taken from a remnant prairie containing both native mutualists and pathogens, soil enhanced with arbuscular mycorrhizal (AM) fungi derived from remnant prairies, and uninoculated controls. For both species, plants inoculated with native prairie AM fungi performed much better than those in uninoculated soil for all parts of the life cycle. Plants in the native whole prairie soil were either generally similar to plants in the uninoculated soil or had slightly higher survival or reproduction. Overall, these results suggest that native prairie AM fungi can have important positive effects on the fitness of early successional plants. As inclusion of prairie AM fungi and pathogens decreased plant fitness relative to prairie AM fungi alone, we expect that native pathogens also can have large effects on fitness of these annuals. Our findings support the use of AM fungi to enhance plant establishment in prairie restorations. Abstract : Composition of the soil microbiome is important to the fitness and success of annual prairie plants. In a field experiment, plants inoculated with native prairie arbuscular mycorrhizal fungi (AMF) perform better than plants inoculated with native prairie soil (containing both native AMF mutualists and native pathogens) and uninoculated plants. This research suggests that native prairie AMF mutualists can have important positive effects on the fitness of early successional native plants, and supports the use of mycorrhizal fungi to enhance native plant establishment in restoration environments.